Public Consumer Behavior in Online Shopping Trends in the Digital Era - Hanisa Syava Farhata Indilah; Nisa; Sri Damayanti (Jurnal Dialektika: Jurnal Ilmu Sosial, 2024)
This study aims to analyze consumerist behavior in online shopping trends in the digital era, focusing on urban communities in Kota Bandung. The research employs a qualitative approach using in-depth interviews, observation, and documentation techniques involving active e-commerce users. Data were analyzed using the interactive model of Miles and Huberman. The findings reveal that consumer behavior is no longer driven by rational needs but by symbolic value (sign value) associated with identity and lifestyle. Specifically, the study finds that (1) purchasing decisions are largely driven by digital promotions that create a sense of artificial urgency, (2) social media plays a significant role in constructing artificial needs through mechanisms of simulation and hyperreality, and (3) the use of paylater services contributes to a shift in the meaning of debt from a financial burden to a normalized digital lifestyle practice. These conditions lead to increased individual spending and a transformation of social values, where consumption functions as a means of identity expression and social recognition. From the perspective of Jean Baudrillard, this phenomenon reflects a consumer society dominated by symbols, images, and simulation within the context of digital urban life.